Diversity of medicinal plants and their uses by the Sanger tribe of Sangihe Islands, North Sulawesi, Indonesia - DINGSE PANDIANGAN; MARINA SILALAHI; FARHA DAPAS; FEBBY KANDAU (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Pandiangan D, Silalahi M, Dapas F, Kandou F. 2019. Diversity of medicinal plants and their uses by the Sanger tribe of Sangihe Islands, North Sulawesi, Indonesia. Biodiversitas 20: 621-631. The Sanger tribe is an indigenous tribe in Sangihe Islands, North Sulawesi, who still continue to use traditional medicinal plants. The objectives of this study were to document the diversity of medicinal plants and their general uses by the Sanger tribe in the selected villages of Sangihe Islands and to identify plants that have anti-cancer potential. The study was conducted with ethnobotanical approach using survey and interviews among 90 respondents selected from 9 study villages located in 3 sub-districts of Sangihe Islands. The study showed that 118 species of medicinal plants belonging to 47 families had been used by the Sanger tribe to treat 39 different types of diseases. Thirteen (13) species each were used for treating fever and ulcers, 12 species in the treatment of poisoning, 10 species each for cough and kidney diseases, 8 species for each of the diabetes mellitus and cancer or tumors, and 7 species each for itching, hypertension, physical injury and blood circulation disorders. For other diseases, the number of plant species used as medicines varied from 1 to 6. Leaves were the most predominantly used part for medicinal purposes as this was used in case of 73 species, followed by stems (37 species), roots (29 species), flowers (25 species), fruits (20 species) and seeds (17 species). Twenty percent (20% of the recorded medicinal plants were consumed directly and others after different methods of processing and preparation, such as boiling (51%), crushing (15%), roasting (2%), soaking (16%) and pasting (7%), and a species can be used more once. A utilization of Dischidia nythesiana as medicines for cancer/tumor by the Sanger tribe has not been reported before.